(untitled) (Research, Society and Development, 2021)
The Brazilian Astronomy Olympics and Astronautics (OBA) had its first edition in 1998, promoting in Brazil an educational event, with a scientific focus, already consolidated internationally. The Group of the Tutorial Education Program of Knowledge “Conexão de Saberes em Física e Popularização da Ciência” at Unifei (“Campus Avançado de Itabira”) created a students assistance and preparation program with workshops and gymkhanas on Astronomy. Based on a methodology to add the pleasure of learning with the constant study of the students in proposed themes, this program aims to solve the difficulties in the process of student training, in the assimilation and construction of scientific knowledge and in the teaching-learning process. Based on this program, several important reactions were observed and this work aims to show analysis related to the performance of its participants at OBA. An increase in average grades was verified among the students from the 7th to 9th grades, especially the seventh graders, who performed 36% better. Consequently, there was an expressive increase in the number of won medals, from 1 medal for 50 participants in 2015 to 1 medal for 4 participants in 2019.